Description of Prescribing Practices in Patients with Upper Gastrointestinal Bleeding Receiving Intravenous Proton-Pump Inhibitors: A Multicentre Evaluation - Robert Enns; Christopher N Andrews; Martin Fishman; Michael Hahn; Kenneth Atkinson; Peter Kwan; Adrian Levy (Canadian Journal of Gastroenterology)
BACKGROUND: Intravenous forms of proton pump inhibitors (IV PPI) are routinely used for patients with acute upper gastrointestinal bleeding, but a significant concern for their inappropriate use has been suggested.